Designing social protection to promote women’s resilience to risk - Roy, Shalini; Quisumbing, Agnes R.; Hoddinott, John F.; Ahmed, Akhter; Bakhtiar, M. Mehrab; Hidrobo, Melissa; Rakshit, Deboleena; Berhane, Guush; Gilligan, Daniel O.; Grimachew, Fikirte; Kumar, Neha; Ambler, Kate; et al. (CGIAR System Organization, 2024)
Evidence-based guidance on effective social protection design for implementers to promote women’s resilience to risk.